The implication of play and fantasy in the construction of the meaning of children's enunciation - Almeida, Suzana Rosa de; Romero, Marcia [UNESP] (Univ Estadual Oeste Parana-unioeste, 2016)
The aim of this paper is to contribute to the understanding of issues related to the meanings of children's enunciation, considering particularly the role of play and fantasy. To achieve this, we have based ourselves on theoretical and conceptual contributions from the Theory of Enunciative Operations in association with cognitive psychology, through its position towards the construction process of the enunciations and their meaning (CULIOLI, 1990; DE VOGUE, FRANCKEL, PAILLARD, 2011) - and towards interactions characterized as routinized, integrated into the concept of format (BRUNER, 1983), still stressing the relationship between play, fantasy and language in early childhood (WINNICOTT, 1982). Throughout this study we presented the analysis of the speech of a male child, GUS, registered between 24 and 35 months of age, provided by published audiovisual data, recorded and transcribed through the CLAN system, that is part of NALingua, a databank that is integrated to interdisciplinary research project coordinated by DEL RE (UNESP/FCLAr-CNPq). The analysis focuses on GUS interactions that are observed at the play with different car toys, a themed card game, also about cars, and the animated film's plot Cars(PIXAR, DISNEY, 2006), that are presented within a wide range of supports for the child to interact with, stimulating his verbal and nonverbal production. By examining its presence in the process of acquiring structural aspects of the language, we demonstrated how the child is able to adopt representations accessed by the use of words and expressions, due to an intersubjective process of adjustment that integrates fantasies and ludic experiences.
Keywords: acquisition of mother language; children's enunciations; meaning construction process